(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Cloud plays a vital role in many domains such as weather forecasting, power forecasting, agriculture, and so on. The fraction/ amount/ percentage of cloud cover over a region is a weather parameter to be considered for forecasting applications. Under suitable weather conditions the cloud cover plays a vital role is precipitation nowcasting. The relation between the cloud cover and precipitation can be directly related under suitable weather conditions. Here, we propose to estimate fraction/amount/percentage of cloud cover based on the ground based images. Pixel saturation is used for cloud cover estimation. Singapore High-dynamic-range Whole sky IMaging SEGmentation Database SHWIMSEG dataset images were used for testing the system proposed. Cloud cover in the range of no cloud cover 0% to full cloud cover 100% was tested. Once the test was carried out on SHWIMSEG dataset, the all sky images acquired from camera module PYRA300C are passed through the system for cloud cover percentage estimation. An accuracy of 92.49% was achieved on the images.